Unmasking nativism in Asia's world city: graffiti and identity boundary un/making in Hong Kong. Issue 3 (3rd May 2020) - Lowe, John; Ortmann, Stephan
ABSTRACT: This work examines the discursive bases to Hong Konger identities by using a repertoire of anti-mainland and pro-democracy graffiti that impose alternative, counter-geographies onto space. Given the spatial specificities of pro-Hong Kong graffiti, the communication of nativist messages is potent in demarcating the boundaries of Hong Kong nativism and mainland 'Otherness' by virtue of how mainland China and its peoples are cognitively experienced and perceived by geographical imaginations of place. As a spatial practice, graffiti writing, it is argued, contests hegemonic representations of space and disrupts representational space through the imposition of 'counterspaces' that subsume a set of power relations which reinforce the boundaries of Hong Kong nativism using geographical imaginations of mainland China blended with truths.